Diagnóstico y propuesta modelo de gestión del conocimiento para el fondo nacional del ahorro. (2020)
The present work consists of a proposal for the National Savings Fund, which allows valuing intellectual capital and aligning efforts with organizational goals. This is based on the fact that knowledge management over time has become a highly important strategy, since it maintains companies' position and encourages organizational learning. Although it is an intangible concept, it allows, among other things, to create and operate one of the most important assets that companies can obtain. Taking into account the above and by means of an exhaustive analysis of the aspects that have a direct impact on the management of explicit knowledge, a model will be being structured that leads to potential skills, with the promotion of personal development and competencies; in a way that encourages continuous improvement and manages to solve the critical points for the explicitation of knowledge.